Evaluation of genetic variability of kenaf (Hibiscus cannabinus L.) from different geographic origins using morpho-agronomic traits and multivariate analysis - Golam, F.; Alamgir, M.A.; Rahman, M.M.; Subha, B.; Motior, M.R. (2011)
Morpho-agronomical characterization was done for 16 kenaf accessions from 4 different geographic origins to assess the variation and genetic relationships according to their origin. To evaluate their genetic relationships, correlation matrix with 13 quantitative traits were used for Principal Component Analysis (PCA) analysis, which produced three groups. Similar grouping pattern was obtained by clustering the accessions using the dissimilarity matrix of Ward's method. Clustering of the accessions with origin showed the association of genetic variability among the accessions with their source of origin. To evaluate the genetic variability among the accessions, fishers distance was calculated with significant p-value. The highest distance was observed among the accessions originated from Australia and China. Discriminant analysis with two major factors revealed that days of 50 % flowering and maturity may be the important traits to differentiate the accessions according to the origins. The late to middle flowering accessions from different origins can be used to grow high fibre yield producing kenaf in the tropical environment.